Dissolution of Silver Nanowires and Nanospheres Dictates Their Toxicity to Escherichia coli. (20th August 2013) - Visnapuu, Meeri; Joost, Urmas; Juganson, Katre; Künnis-Beres, Kai; Kahru, Anne; Kisand, Vambola; Ivask, Angela
Abstract : Silver nanoparticles are extensively used in antibacterial applications. However, the mechanisms of their antibacterial action are not yet fully explored. We studied the solubility-driven toxicity of 100 × 6100 nm (mean primary diameter × length) silver nanowires (NWs) to recombinant bioluminescent Escherichia coli as a target representative of enteric pathogens. The bacteria were exposed to silver nanostructures in water to exclude the speciation-driven alterations. Spherical silver nanoparticles (83 nm mean primary size) were used as a control for the effect of NPs shape. Toxicity of both Ag NWs and spheres to E. coli was observed at similar nominal concentrations: the 4h EC50 values, calculated on the basis of inhibition of bacterial bioluminescence, were 0.42 ± 0.06 and 0.68 ± 0.01 mg Ag/L, respectively. Dissolution and bioavailability of Ag from NWs and nanospheres, analyzed with AAS or Ag-sensor bacteria, respectively, suggested that the toxic effects were caused by solubilized Ag + ions. Moreover, the antibacterial activities of Ag NWs suspension and its ultracentrifuged particle-free supernatant were equal. The latter indicated that the toxic effects of 80–100 nm Ag nanostructures to Escherichia coli were solely dependent on their dissolution and no shape-induced/related effects were observed. Yet, additional nanospecific effects could come into play in case of smaller nanosilver particles.